2018
DOI: 10.1021/acsomega.8b00406
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Binding of Expansin Exl1, from Pectobacterium carotovorum, to Plant Xylem and Comparison to EXLX1 from Bacillus subtilis

Abstract: The plant xylem is a preferred niche for some important bacterial phytopathogens, some of them encoding expansin proteins, which bind plant cell walls. Yet, the identity of the substrate for bacterial expansins within the plant cell wall and the nature of its interaction with it are poorly known. Here, we determined the localization of two bacterial expansins with differing isoelectric points (and with differing binding patterns to cell wall extracts) on plant tissue through in vitro fluorophore labeling and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…In addition, for basic proteins such as BsEXLX1, electrostatic interactions, driven by its positive residues with the negative components of pectin and hemicellulose, result in non-productive binding, while an acidic expansin seems to be repelled by the same acid fraction of the wall [4,31,48]. For instance, experiments with fluorophore-labelled proteins and confocal microscopy showed that whereas BsEXLX1 bound cell walls of most cell types in celery petiole cross sections due to the non-specific electrostatic interaction, PbExl1 signal was confined to the intercellular spaces between xylem vessels and the surrounding cells [50]. PbExl1 localization in xylem structures might be relevant as expansin genes are commonly found in the genomes of xylem-colonizing pathogenic bacteria [4,50].…”
Section: Expansin-related Protein Structure Expansins Structurementioning
confidence: 99%
See 3 more Smart Citations
“…In addition, for basic proteins such as BsEXLX1, electrostatic interactions, driven by its positive residues with the negative components of pectin and hemicellulose, result in non-productive binding, while an acidic expansin seems to be repelled by the same acid fraction of the wall [4,31,48]. For instance, experiments with fluorophore-labelled proteins and confocal microscopy showed that whereas BsEXLX1 bound cell walls of most cell types in celery petiole cross sections due to the non-specific electrostatic interaction, PbExl1 signal was confined to the intercellular spaces between xylem vessels and the surrounding cells [50]. PbExl1 localization in xylem structures might be relevant as expansin genes are commonly found in the genomes of xylem-colonizing pathogenic bacteria [4,50].…”
Section: Expansin-related Protein Structure Expansins Structurementioning
confidence: 99%
“…For instance, experiments with fluorophore-labelled proteins and confocal microscopy showed that whereas BsEXLX1 bound cell walls of most cell types in celery petiole cross sections due to the non-specific electrostatic interaction, PbExl1 signal was confined to the intercellular spaces between xylem vessels and the surrounding cells [50]. PbExl1 localization in xylem structures might be relevant as expansin genes are commonly found in the genomes of xylem-colonizing pathogenic bacteria [4,50].…”
Section: Expansin-related Protein Structure Expansins Structurementioning
confidence: 99%
See 2 more Smart Citations
“…Key sites of wall loosening may be limited contact points between cellulose microfibrils 5 . How these interactions result in cell wall loosening still requires further investigation 6 . Expansins were first discovered in plants and were described as proteins mediating pH‐dependent extension and stress relaxation of cell walls 7 .…”
Section: Introductionmentioning
confidence: 99%